Supplement to the third edition of Ethnomusicology - Kunst, Jaap. author. aut Link
45 p. 9 illus.
Keywords: Since the appearance of the third edition of 'Ethnomusicology', still more titles have come to my knowledge, all issued before September 1958. The reader will find them in this Supplement. I have used this opportunity to add some more synopses of training possibilities for ethnomusicologists, together with an additional selective list of recordings issued, as far as I know, in 1958. Finally I may express my gratitude to Messrs. Nijhoff who gave me the opportunity to improve my endeavor to give a practically exhaustive survey of what has been published in the field of ethnomusicology up to August 31, 1958. Amsterdam, December 14, 1959. J.K. v CONTENTS Preface . . . . . . . . . . . . . . . . . . . . . . . . . v Training possibilitics for cthnomusicologists. . . . . . . . . . I Selection of L.P.-records of authentie ethnie musie issued in I958 . 5 Bibliography. . . 8 Illustrations 65-72. . . . . . . . . . . . . . . . . . . . 25 . Index of subjects. . . . . . . . . . . . . . . . . . . . 27 . Index of peoples and regions the music of which has been studied andjor recorded. . . . . . . . . . . 30 Index of authors, collectors and musicians . . . . . . . . . . 34 Index of periodieals. . . . . . . . . . . . . . . . . . . 39 .